Analisa Produktifitas Tenaga Kerja Sektor Manufaktur di Indonesia - Syafitri, Wildan (UI Scholars Hub, 2003)
Labor productivity could be direct measurement of human capital quality as it shows the amount of output that the labor can prduce. McConnel and Brue (1995) define labor productivity as ratio between produced output and working hour at certaint level of wage. Our research try to analyze the labor productivity on manufacture sector and its explanatory variables by applying cross section data of medium scale industries on 1996 in Indonesia. The estimation result shows the positive significance of education level, the more educated labor will yield higher productiviy. We also try to internalize gender issue and we find the more female worker employed, the less productivity of labor force, and consequently will lowering the wage level. Those findings confonn not only Human Capital theory by Nelson-Phelps (1966), Lucas (1998) and Aghion and Howitt (1998), but also confonn the theory of wage discrimination based on gender as previously stated by Byron and Takahashi (1989) and Hansen and Wahlberg (1997).